Trees for livelihoods: Exploring the relationship between community agroforestry and community capitals in rural Haiti. Issue 5 (20th October 2022) - Blaise, Gloria C.; Allred, Shorna B.
ABSTRACT: For decades, various institutions have attempted to improve rural livelihoods in Haiti by implementing agroforestry. While agroforestry provides ecological and economic benefits, little is known about the long-term livelihood outcomes of agroforestry interventions in Haiti. Using the Community Capitals Framework (CCF), this study investigated multiple dimensions of agroforestry outcomes in practicing communities and compared them to communities not practicing agroforestry, in reference to a community-based agroforestry program initiated by the Haiti Timber Reintroduction Program (HTRIP). Data were collected using qualitative research methods of in-depth interviews and focus groups. The results indicate that community agroforestry makes positive contributions to all community capitals–some (social, human, financial, natural, cultural) more than others (built, political). We recommend that institutions pay particular attention to building social, human, and natural capital and how they contribute to financial capital, as this was the entry point for the spiraling up of capitals in rural Haitian communities.